Exploring the main features of the post-industrial economy - Mekhovych, S. A.; Pererva, P. G.; Shapoval, V. S. (Видавничий дім "Києво-Могилянська академія", 2023)
It is proven that the new technological base contributed to the intellectualization of labor and required an increase in the level of education of workers. The interest of the world scientific community in the problem of intellectual resources is connected with the transition of the most developed countries of the world to the post-industrial economy (or information economy, digital economy, knowledge economy), which is distinguished by certain features.
Дослідження основних рис постіндустріальної економіки
Keywords: economy; post-industrial society; development risks; industry; market